Millets Can Have a Major Impact on Improving Iron Status, Hemoglobin Level, and in Reducing Iron Deficiency Anemia–A Systematic Review and Meta-Analysis - Anitha, Seetha; Kane-Potaka, Joanna; Botha, Rosemary; Givens, D. Ian; Sulaiman, Nur Liana Binti; Upadhyay, Shweta; Vetriventhan, Mani; Tsusaka, Takuji W.; Parasannanavar, Devraj J.; Longvah, Thingnganing; Rajendran, Ananthan; Subramaniam, Kowsalya; et al. (Frontiers in Nutrition, 2021)
The prevalence of iron deficiency anaemia is highest among low and middle-income countries. Millets (including sorghum) are a traditional staple in many of these countries and known to be rich in iron. However, a wide variation in the iron composition of millets has been reported, which needs to be understood in consonance with its bioavailability and roles in reducing anaemia. This systematic review and meta-analysis was carried out to analyze the scientific evidence on the bioavailability of iron in different types of millets, processing and the impact of millet-based food on iron status and anaemia. The results indicated that iron levels in the millets used to study iron bioavailability (both in vivo and in vitro) and efficacy varied with the type and variety from 2 mg/100 g to 8 mg/100 g. However, not all the efficacy studies indicated the iron levels in the millets. Thirty research studies including 22 human interventions and 8 in vitro studies were included in the meta-analysis, with various outcomes such as haemoglobin level, serum ferritin level, and absorbed iron. The studies included finger millet, pearl millet, teff and sorghum or a mixture of millets. Twelve of the efficacy studies conducted on anaemic individuals significantly (p <0.01) increased haemoglobin levels by 13.2% following regular consumption (21 days to 4½ years) of millets either as a meal or drink compared to regular diets. Seven studies on adolescents showed increases in haemoglobin levels from 10.8 ± 1.4 (moderate anaemia) to 12.2 ± 1.5 g/dl (normal). Two studies conducted on humans demonstrated that consumption of a pearl millet-based meal significantly increased the bioavailable iron (p<0.01), with the percentage of bioavailability being 7.5 ± 1.6, and provided bioavailable iron of 1.00 ± 0.4 mg. Four studies conducted on humans showed significant increases in ferritin level (p <0.05) upto 54.7%. Eleven in-vitro studies showed that traditional processing methods such as fermentation and germination can improve bioavailable iron significantly (p < 0.01) by 3.4 and 2.2 times and contributed to 143% and 95% of the physiological requirement of women, respectively. Overall, this study shows millets can reduce iron deficiency anaemia.